Pengaruh Kualitas Pelayanan Kesehatan Terhadap Kepuasan Pasien Keluarga Berencana di Puskesmas Sulamu Tahun 2021 - Yerli Nixelery Ramly; Yoseph Kenjam; Tadeus A.L Regeletha (Yayasan Literasi Sains Indonesia, 2023)
Service quality is a very unique event, because there are dimensions and indicators that can differ among the people involved in the service. Service quality is inseparable from the level of perfection of health services in meeting a need and every demand of every use of the service. This study aims to determine the effect of service quality on family planning patient satisfaction at the Sulamu Health Center in 2021. This study used a quantitative research method with a cross-sectional study design. The research was conducted at the Sulamu Health Center from December 2021- October 2022. The population in this study was 515 patients. The number of samples in this study were taken using the slovin formula, namely 225 patients.sampling technique is accidental sampling technique. The results showed that there was an effect of the quality of health services on the satisfaction of family planning patients seen from the dimensions of physical evidence at the Sulamu Health Center, which was a sig 0.000, there was an effect of the quality of health services on the satisfaction of family planning patients, seen from the reliability dimension at the Sulamu Health Center was a sig 0.000 , there is an effect of the quality of health services on patient satisfaction with family planning seen from the dimension of responsiveness at the Sulamu Health Center which is a sig 0.941, there is an effect of the quality of health services on patient satisfaction with family planning seen from the dimensions of guarantees at the Sulamu Health Center there is a sig value of 0.004, there is an influence the quality of health services on family planning patient satisfaction seen from the dimensions of empathy at the Sulamu Health Center is a sig value of 0.100.